The Effect Of Financial Distress And Information Technology On Financial Statement Fraud With Corporate Governance As A Moderating Variable - Febrina Thogamas Putri; Harti Budi Yanti (PT. Cendekia Sapta Indonesia, 2025)
This study aims to delineate the extent to which financial distress and information technology contribute to financial statement fraud, with corporate governance serving as a moderating variable. The analysis centers on BUMN listed on IDX, utilizing secondary data drawn from audited annual reports accessible via official IDX records and the respective corporate websites. The population comprises BUMN entities listed from 2021 to 2024, with samples selected through purposive sampling. The study employs panel data regression analysis, utilizing the EViews10 application as an analytical tool. The findings reveal that financial distress bears a significant relationship with financial statement fraud, a linkage that is notably reinforced in the presence of sound corporate governance. Moreover, information technology is found to influence fraudulent reporting practices, although corporate governance does not appear to moderate this particular effect. The findings underscore the pivotal role of corporate governance as a strategic safeguard against the manipulation of financial statements, especially in times marked by heightened financial distress. Accordingly, the cultivation of strong governance frameworks may serve as a safeguard against the escalation of fraudulent financial behavior.